Be aware of the sodium intake outside student canteens: development and validation of a sodium food frequency questionnaire in Chinese undergraduates - Xi, Yue; Xiang, Caihong; Liang, Jiajing; Huo, Jiaqi; Yong, Cuiting; Zou, Hanshuang; Pan, Yunfeng; Wu, Minchan; Xie, Qingqing; Deng, Jing; Yang, Lina; Chen, Jihua; et al. (Frontiers in Nutrition, 2023)
Background Chinese college students used to eat in student canteens, making dietary consumption outside the cafeterias the main reason for the difference in sodium intake. This study aims to develop and validate a food frequency questionnaire (Sodium-FFQ) targeting dietary sodium intake outside the canteens among undergraduates in China. Methods This cross-sectional study included 124 and 81 college students from comprehensive universities in the development and validation stage. A 24 h dietary recall and a food frequency questionnaire were used to develop the Sodium-FFQ. Food items were selected according to the foods that contributed more to the total sodium intake. Test–retest correlation coefficients with an interval of 14 days were employed to evaluate reproducibility. Validity was assessed against a single 24 h urine collection and a 3-day dietary record using correlation coefficients, Bland–Altman analyses, and cross-classification analysis of Kappa coefficients. Results The Sodium-FFQ consists of 12 groups of foods with 48 items. The Spearman correlation coefficient of test–retest on sodium intake was 0.654 (p < 0.05), and that between the Sodium-FFQ, 3 × 24 h dietary record, and 24-h urinary sodium were 0.393 (p < 0.05) and 0.342 (p < 0.05), respectively. The Sodium-FFQ was correlated to 24 h urinary sodium-to-potassium ratio, with a Spearman coefficient of 0.370 (p < 0.05). The classification agreement of the Sodium-FFQ and 24 h urinary sodium was 68.4%, and the Kappa coefficient was 0.371 (p < 0.001). Conclusion The Sodium-FFQ developed in this study presented an acceptable reproducibility, validity, and classification agreement. It indicates that the Sodium-FFQ could be a potential tool for promoting sodium restriction in college students.